Lower Extremity Flap Salvage in Thrombophilic Patients: Managing Expectations in the Setting of Microvascular Thrombosis - DeFazio, Michael V.; Hung, Rex W. Y.; Han, Kevin D.; Bunting, Haley A.; Evans, Karen K. (Journal of Reconstructive Microsurgery, 2016)
Background Undiagnosed thrombophilia is a risk factor for flap failure; however, its prevalence in patients undergoing microsurgical reconstruction is unknown. We present our experience with free tissue transfer (FTT) in a high-risk population of lower extremity patients with documented thrombophilia, identified through preoperative screening.Methods Between January 2012 and April 2014, 41 patients underwent 43 free flaps for nontraumatic, lower extremity reconstruction by a single surgeon. Patients were preoperatively screened for thrombophilia using historical information and standardized laboratory testing. Demographic data, perioperative management, outcomes, and salvage rates for thrombophilic and nonthrombophilic cohorts were compared.Results Routine preoperative screening identified 52 thrombophilic traits among 25 patients in this series (61%). The most common traits were the plasminogen activator inhibitor-1 4G/5G variant (n = 12) and the methylenetetrahydrofolate reductase A1298C (n = 10) and C677T (n = 9) polymorphisms. While success rates were similar between thrombophilic and nonthrombophilic patients (84 vs. 94%; p = 0.15), thrombotic complications (25 vs. 14%; p = 0.09) and flap failure following postoperative thrombosis (100 vs. 33%; p = 0.05) appeared to be more common in patients with thrombophilia. On average, microvascular complications manifested later in the setting of thrombophilia (mean 4.8 days vs. 18 hours; p = 0.20) and were associated with a worse overall prognosis (salvage rate, 0 vs. 67%; p = 0.05).Conclusions Despite high success rates, thrombophilia appears to increase the risk of nonsalvageability following lower extremity FTT. This information should be used to help counsel patients regarding the risks and benefits of microsurgical reconstruction, as salvage rates following postoperative thrombotic events approach 0% in the presence of thrombophilia.
Keywords: flap salvage; free tissue transfer; hypercoagulability; microsurgery; thrombophilia